Mother-Child Play: A Comparison of Autism Spectrum Disorder, Down Syndrome, and Typical Development - Bentenuto, Arianna; De Falco, Simona; Venuti, Paola (Frontiers in Psychology, 2016)
The purpose of the present study was to analyze mother-child collaborative play in children with Autism Spectrum Disorders (ASD) compared to children with Down Syndrome (DS) and typical developing children (TD). Children with ASD are often described as having deficient play skills, particularly in the symbolic domain. Caregivers' involvement in child play activities increases the structural complexity of playing in both typically developing children and children with disabilities. Participants included 75 mothers and their children with ASD (n = 25), with Down Syndrome (n = 25) and with typical development (n = 25). Mother–child play sessions were analyzed using a coding system for exploratory and symbolic play. Results indicated that children with ASD showed more exploratory play compared to children in the other groups. No significant differences emerged between the three groups for child symbolic play or for mother play. These findings are discussed in relation to the debate about functional and symbolic play in children with ASD and in relation to the importance of setting and age for play assessment.